Innovation of a modular microwave-assisted pyrolysis (MAP) reactor based on coconut shell biochar with IoT monitoring system integration for the conversion of non-B3 plastic into alternative bio-fuels - Noufal Aufarisyi Ahmadiansyah; Gabby Ester Gracia; Supriyono (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Indonesia produces more than 12.3 million tons of plastic waste each year, but only a mere 14% is recycled, leading to serious environmental concerns. On a global scale, solid waste totals 2.3 billion tons annually, with merely 61% being properly managed. This situation underscores the pressing demand for sustainable and effective technologies for handling plastic waste. Traditional pyrolysis is widely utilized but struggles with high energy requirements, needing temperatures between 700-900 °C, inconsistent heat distribution, and overall low efficiency in the process. Methods: This research introduces a Microwave-Assisted Pyrolysis (MAP) reactor that utilizes KOH-activated coconut shell biochar as a microwave absorber. It achieves a surface area greater than 800 m²/g, enabling effective absorption of 2.45 GHz microwaves. Non-toxic plastics like HDPE and PP are subjected to pre-treatment before undergoing MAP processing at temperatures of 450-600 °C for a duration of 10 minutes. An Internet of Things (IoT) system facilitates real-time monitoring of temperature, pressure, and flow rate to maintain precise control throughout the process. Findings: Results from experiments and a review of existing literature indicate that MAP is capable of transforming plastics into 70% bio-oil, 10% syngas, and 20% biochar, with energy consumption only at 0.8-1.2 kWh/kg—30-40% less than what traditional pyrolysis requires. The activation energy for coconut shell biochar drops significantly to 24.5 kJ/mol, compared to 84.2 kJ/mol found in conventional systems, showing better efficiency in volumetric heating. MAP has the potential to cut down plastic pollution by as much as 65% while generating bio-oil as an alternative fuel source, aiding the implementation of a circular economy and supporting Sustainable Development Goals 9, 12, and 13. Conclusion: MAP demonstrates a highly energy-efficient and scalable alternative for plastic waste valorization, reducing environmental pollution while generating useful byproducts and supporting sustainable development objectives. Novelty/Originality of this article: The research stands out by integrating KOH-activated coconut shell biochar with IoT-enabled real-time monitoring and an energy-efficient MAP method, providing a sustainable approach for recovering value from plastic waste beyond traditional pyrolysis.